Structural and Thermodynamic Basis of (+)-α-Pinene Binding to Human Cytochrome P450 2B6 - Wilderman, P. Ross (2013)
Despite recent advances in atomic level understanding of drug and inhibitor interactions with human cytochromes P450, the decades-old questions of chemical and structural determinants of hydrocarbon binding are still unanswered. (+)-α-Pinene is a monoterpene hydrocarbon that is widely distributed in the environment and a potent P450 2B inhibitor. Therefore, a combined biophysical and structural analysis of human P450 2B6 interactions with (+)-α-pinene was undertaken to elucidate the basis of the very high affinity binding. Binding of (+)-α-pinene to the P450 active site was demonstrated by a Type I spectral shift. Thermodynamics of ligand binding were explored using isothermal titration calorimetry and compared to those of P450 2A6, which is much less flexible than 2B6 based on comparison of multiple X-ray crystal structures. Consistent with expectation, entropy is the major driving force for hydrocarbon binding to P450 2A6, as evidenced by the calorimetric results. However, formation of the 2B6-(+)-α-pinene complex has a significant enthalpic component. A 2.0 Å resolution crystal structure of this enzyme ligand complex reveals that the highly plastic 2B6 utilizes previously unrecognized rearrangements of protein motifs. The results indicate that the specific components of enthalpic contribution to ligand binding are closely tied to the degree of enzyme flexibility.